EFFECTIVENESS OF VILLAGE FUND MANAGEMENT IN LAIKIT VILLAGE, DIMEMBE DISTRICT, NORTH MINAHASA REGENCY - Samita Wehelmina Abigael Tanod; Wilson Bogar; Meidy S. S. Kantohe (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the effectiveness of Village Fund management in Laikit Village, Dimembe District, North Minahasa Regency. The research is motivated by audit findings from the North Minahasa Regency Inspectorate for the 2023-2024 period, which revealed administrative and substantive irregularities, including the non-realization of a community empowerment program worth IDR 250 million and the detention of the Village Head by law enforcement authorities in November 2025. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews with five key informants, field observations, and document analysis. The findings indicate that the effectiveness of Village Fund management in Laikit Village falls into the moderate category. Administrative mechanisms such as Village Deliberations, the installation of transparency media, and the Siskeudes reporting system have been implemented. However, substantive dimensions remain underdeveloped: citizen participation procedural remains and dominated by local elites, transparency is not inclusive due to technical information that is difficult for ordinary residents to understand and unevenly distributed media, and the quality of infrastructure varies without a systematic maintenance mechanism.